(untitled) (SCIÉNDO INGENIUM, 2023)
The objective of this research is to identify the value activities that are integrated in the Productive Chain of the bottling companies in Trujillo and that include the recovery systems of plastic bottle waste. In this way, we have a Supply Chain and Reverse Logistics design to increase productivity by integrating the principles of Circular Economy. The research methodology is based on the study of two cases and the elaboration of structured questionnaires, statistically processed with the SPSS Software and the Chi-Square Test for the verification of the hypothesis and thus determine the competitive situation in relation to the strategy and business logistics. With the application of Discounted Cash Flow, the CAPM (Capital Asset Pricing Model) and for the sensitivity and risk analysis with the Crystal Ball tool, an increase in economic productivity measured through profitability indicators and the Added Value of shareholders was observed. In addition, it is demonstrated that the management of end-of-life products achieves environmental benefits with savings in CO2 emissions and sustainable profitability for the industry.